Analyzing the Effectiveness of Formative and Summative Assessments for EFL Speaking Skills: A Qualitative Study at Hamzanwadi University - Yadi, Yogi Didi; Husnu, Muhammad; Yusri, Ahmad; Fikni, Zahratul (Journal of English Language and Education, 2025)
This study investigates the use of formative and summative assessments in enhancing the speaking skills of sixth-semester EFL students at Hamzanwadi University. Although numerous studies have explored assessment practices in language learning, limited attention has been given to how both formative and summative assessments specifically influence EFL learners’ speaking performance in the Indonesian higher education context. To address this gap, the study employed a qualitative descriptive design, collecting data through questionnaires and interviews to explore students’ perceptions, experiences, and reflections regarding both assessment types. Findings reveal that formative assessment has a greater positive impact on speaking performance, offering regular feedback, progressive practice, and improved confidence while reducing anxiety. Summative assessment, while motivating, often induces stress, limits feedback, and may not fully reflect students’ actual abilities. The study concludes that formative assessment is more effective in supporting speaking development and recommends a balanced approach that emphasizes formative processes while using summative evaluation as a complementary measure.